The Effect of Solvent Variation on Flavonoid Content of Purslane Herb (Portulaca grandiflora Hook.) - Indriasari, Christina (Universitas STRADA Indonesia, 2022)
Purslane is from the Portulaceae family which contains active phenolic compounds and has different antioxidant activities. Portulaca grandiflora Hook. is one of the species of purslane where all parts of the plant are useful. Purslane herb (Portulaca grandiflora Hook.) contains active compounds of alkaloids, flavonoids, tannins, terpenoids, and saponins. Flavonoids act as antioxidants. This study aims to determine the differences in flavonoid levels of extracts resulting from soxhletation of purslane (Portulaca grandiflora) herb with different solvents. This research is an experimental study with soxhletation extraction process and assay using a UV-Vis spectrophotometer with various concentrations of 5, 10, 15, 20, 25, and 30 ppm at a wavelength of 424.5nm. The flavonoid content in each extract of n-hexane, ethyl acetate, and 96% ethanol was 17.91% w/w; 23.27% w/w; 11.67% w/w.